2015
DOI: 10.1371/journal.pone.0133264
|View full text |Cite
|
Sign up to set email alerts
|

HCV NS5A Up-Regulates COX-2 Expression via IL-8-Mediated Activation of the ERK/JNK MAPK Pathway

Abstract: Chronic hepatitis C virus (HCV) infection leads to intrahepatic inflammation and liver cell injury, which are considered a risk factor for virus-associated hepatitis, cirrhosis, and hepatocellular carcinoma worldwide. Inflammatory cytokines are critical components of the immune system and influence cellular signaling, and genetic imbalances. In this study, we found that cyclooxygenase-2 (COX-2) and interleukin-8 (IL-8) were significantly induced by HCV infection and HCV NS5A expression, and induction of COX-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
(50 reference statements)
0
27
0
Order By: Relevance
“…The aberrant expression of COX-2 observed in chronic hepatitis C patients was associated with an increased risk of HCC (Bae et al, 2001). As mentioned earlier, the HCV protein greatly stimulated COX-2 expression and in turn, COX-2 overexpression enhanced HCV replication (Chen et al, 2015). Because of these observations, our previous studies have proved that several natural products can effectively suppress HCV replication by inhibiting NF-kB-mediated COX-2 expression, which supported targeting the COX-2 signaling pathway as a promising approach to develop therapeutic or chemopreventive agents against HCV-positive HCC formation (Lee et al, 2011; Lin et al, 2013).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The aberrant expression of COX-2 observed in chronic hepatitis C patients was associated with an increased risk of HCC (Bae et al, 2001). As mentioned earlier, the HCV protein greatly stimulated COX-2 expression and in turn, COX-2 overexpression enhanced HCV replication (Chen et al, 2015). Because of these observations, our previous studies have proved that several natural products can effectively suppress HCV replication by inhibiting NF-kB-mediated COX-2 expression, which supported targeting the COX-2 signaling pathway as a promising approach to develop therapeutic or chemopreventive agents against HCV-positive HCC formation (Lee et al, 2011; Lin et al, 2013).…”
Section: Introductionmentioning
confidence: 71%
“…In Trujillo-Murillo et al (2007) study, the HCV genomic RNA and COX-2 were co-transfected in Huh-7 cell and the viral RNA replication were elevated with COX-2 induction in concentration-dependent manner. Besides, we recently showed that suppression of COX-2 could be a useful approach for development of HCV inhibitors (Chen et al, 2015; Lin et al, 2015). Furthermore, COX-2 metabolite PEGs is a risk factor to develop HCC (Loginov and Vysotskaia, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our results suggest that JNK pathway is more essential for PRRSV induced IL-8 expression as JNK and c-Jun inhibitor and siRNA knockdown of c-Jun and c-Fos significantly reduced IL-8 expression. Similarly, under stimulation of HIV-1, HCV and Papillomavirus, the expression of IL-8 is also JNK dependent (Chen et al, 2015;Gangwani and Kumar, 2015;Saeed et al, 2015;Zhang et al, 2014). JNK isoforms are strongly activated in response to various cellular stresses (Cargnello and Roux, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other cytokines, such as IFN-β and IFN-γ, displayed an antagonistic effect on the expression of IL-8 [75][76][77]. Analogously, HCV-encoded E2 and NS5A inhibited expression of IFN-β and downstream ISGs through upregulation of IL-8 [78][79][80]. In addition, as shown in HEV infection, AP-1 was required for IFN-β gene transcription as it binds to the PRD IV element of the IFN-β promoter, inducing assembly of IFN-β enhanceosome [81].…”
Section: Hev-mediated Irf Activationmentioning
confidence: 99%